2022
DOI: 10.2478/jvetres-2022-0045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulence genes among Escherichia coli strains isolated from food and carcass swabs of different animal origins in Croatia

Abstract: Introduction Escherichia coli is present in the normal intestinal flora but some strains can cause intestinal and extraintestinal diseases, and research on its presence in food of animal origin is in the interests of public health. This study was designed to characterise E. coli strains according to their origin, their carriage of virulence genes specific for certain pathogroups, and phylogenetic group affiliation. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The isolates belonged to two main phylogroups, A and B1, unlike the predominance of B2 which is commonly reported in human pathogenic E. coli , especially the ExPEC but also those of intestinal disease agents. These findings are consistent with other studies [ 18 , 40 , 41 ] that have reported predominance of phylogroups A and B1 in food animals.…”
Section: Discussionsupporting
confidence: 93%
“…The isolates belonged to two main phylogroups, A and B1, unlike the predominance of B2 which is commonly reported in human pathogenic E. coli , especially the ExPEC but also those of intestinal disease agents. These findings are consistent with other studies [ 18 , 40 , 41 ] that have reported predominance of phylogroups A and B1 in food animals.…”
Section: Discussionsupporting
confidence: 93%
“…Escherichia coli is a bacterial species that typically lives in both human and animal digestive tracts. However, under some conditions, E. coli can spread outside of the digestive system ( 21 ). Numerous studies have shown that milk is an advantageous medium for the growth of E. coli and that an overabundance of these bacteria in this foodstuff can be harmful to the general public’s health ( 18 , 28 ).…”
Section: Introductionmentioning
confidence: 99%